Evaluation of services in tourism: a conceptual map from theory to practice - Santana, Juliana Cardoso de; Maracajá, Kettrin Farias Bem; Machado, Petruska de Araujo (Revista Turismo em Análise, 2020)
The tourism market is on the rise and, therefore, companies seek to improve the perception of their customers’ perceptions about the quality perceived during the consumption of the service. The study proposed a conceptual map on assessing the quality of services in tourism, discussing how theoretical and practical perspectives. For that, a Systematic Literature Review was used, contemplating an analysis of 148 scientific articles and, building a portfolio with 10 national and 10 international articles. Thus, a conceptual map was generated that outlines the main principals in the area. Finally, the synthesis and discussion of the results were based on three study approaches: theoretical, events and models for the evaluation of quality in tourist services. This research offers theoretical and practical contributions through the conceptual map, helping to understand the main approaches of the study currents and, in practice, encourages managers to effectively evaluate the quality of the services offered in their respective enterprises.